2015
DOI: 10.1016/j.triboint.2014.09.019
|View full text |Cite
|
Sign up to set email alerts
|

An analytical study of tribofilms generated by the interaction of ashless antiwear additives with ZDDP using XANES and nano-indentation

Abstract: Mixtures of zinc dialkyl dithiophosphates (ZDDP) and ashless fluorothiophosphates and thiophosphates were examined under tribological conditions. The tribofilms were studied using nanoindentation, electron microscopy and XANES spectroscopy. With the addition of ashless fluorothiophosphates and thiophosphates there is significant reductions in wear at identical phosphorous levels. Tribofilms formed with mixtures of ZDDP and ashless antiwear additives had stable pad like structures while those from ZDDP alone we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 56 publications
1
25
0
1
Order By: Relevance
“…The differences in friction coefficients were small and lower friction coefficient of PCR can be attributed to zincphosphate coating, including Zn and P elements in the composition where they reacted with iron surfaces and formed iron phosphates antiwear pads. It also reacted as a friction modifier like phosphorus containing lubricating oil additive, during the tests as explained by Davis 28 and Sharma et al 29 in their study. Observed abrasive wear scars were parallel to the sliding direction and in different angle with honing marks.…”
Section: Evaluation Of Coefficient Of Friction and Wear Ratesmentioning
confidence: 81%
“…The differences in friction coefficients were small and lower friction coefficient of PCR can be attributed to zincphosphate coating, including Zn and P elements in the composition where they reacted with iron surfaces and formed iron phosphates antiwear pads. It also reacted as a friction modifier like phosphorus containing lubricating oil additive, during the tests as explained by Davis 28 and Sharma et al 29 in their study. Observed abrasive wear scars were parallel to the sliding direction and in different angle with honing marks.…”
Section: Evaluation Of Coefficient Of Friction and Wear Ratesmentioning
confidence: 81%
“…Chemical composition measurements were conducted by FY and TEY mode XANES to detect the valence states of the sulfur element on different depths of tribofilm. Compared with the methods reported in previous studies [22][23][24], the experimental data were obtained at different detection modes of the same beam line station, and the data of different depth surfaces could be compared and analyzed with the K-edge of the sulfur element [25]. An X-ray beam was monochromatized by a fixed-exit double-crystal Si(111) monochromator, and it covered the photon region of 2,460-2,490 eV with 0.30 eV resolution.…”
Section: Xanes Analysismentioning
confidence: 99%
“…[25][26][27][28][29] ZDDP is a widely used anti-wear additive that offers secondary benefits such as antioxidant, corrosion inhibition and extreme pressure protection. [30][31][32][33][34] ZDDP is outstanding at forming stable hard glassy protective tribofilms on the surfaces. 33,35 Large-scale production of ZDDP since its development in the early 1940s has made it significantly cheaper in comparison to other additives.…”
Section: Introductionmentioning
confidence: 99%
“…18,41 Several studies investigating ashless additives have been shown to have comparable or better anti-wear, antioxidant and extreme pressure properties as compared to ZDDP, however understanding the mechanisms for wear protection with these additives remains a challenge. 36,[42][43][44] X-ray absorption near edge structure (XANES) spectroscopy has been effectively used by Najman et al, 21,23,45,46 Sharma et al, 30,47,48 and Kim et al, 22,36,49 for characterising spatial distribution of chemical species in tribofilms derived from ashless antiwear additives. They concluded that the tribofilms contained short or long chain polyphosphates and iron sulfates.…”
Section: Introductionmentioning
confidence: 99%